The oligarchic tendencies lead to the social movements of the Industrial Trends: Global Point of View - Elies, Martin (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
The article discusses oligarchy and Egalitarian social movement, Poverty, Increasing Deprivation, and Egalitarian Movement the discussion contains oligarchy tendency, in order to trace the general effects of industrial trends, deviations from the previous Commercial Revolution are necessary as they mark the origins of the nation-state and trends. The industrialization and revolution. Oligarchy, Ideology, and the Emergence of Political Parties. Industrial trends resulted in a necessary but repressive division of the workforce and created a wage-dependent working class in urban environments. The English Revolution of the seventeenth century and the American and French Revolutions of the eighteenth century the bourgeois revolution with a political doctrine based on the natural rights of life, liberty. property, revolution, and popular sovereignty